Congenital lipoid adrenal hyperplasia - Chan Jong Kim (Korean Society of Pediatric Endocrinology, 2014)
Congenital lipoid adrenal hyperplasia (lipoid CAH) is the most fatal form of CAH, as it disrupts adrenal and gonadal steroidogenesis. Most cases of lipoid CAH are caused by recessive mutations in the gene encoding steroidogenic acute regulatory protein (StAR). Affected patients typically present with signs of severe adrenal failure in early infancy and 46,XY genetic males are phenotypic females due to disrupted testicular androgen secretion. The StAR p.Q258X mutation accounts for about 70% of affected alleles in most patients of Japanese and Korean ancestry. However, it is more prevalent (92.3%) in the Korean population. Recently, some patients have been showed that they had late and mild clinical findings. These cases and studies constitute a new entity of 'nonclassic lipoid CAH'. The cholesterol side-chain cleavage enzyme, P450scc (CYP11A1), plays an essential role converting cholesterol to pregnenolone. Although progesterone production from the fetally derived placenta is necessary to maintain a pregnancy to term, some patients with P450scc mutations have recently been reported. P450scc mutations can also cause lipoid CAH and establish a recently recognized human endocrine disorder.